SUFISME DAN NEO-SUFISME DALAM PUSARAN CENDIKIAWAN MUSLIM - Muhammad Ilham Usman (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2019)
In the modern era, human being frequently encounter a number of problems in terms of modernization. The welfare, which is fully of materialistic things, does not contribute to the happiness of the people apart  from people background or different level in the community. In this regards, this article mainly concern on Sufism in the Islam discipline. Sufism itself tries to emphazise the purification of spirituality based on universal values. This effort will then be implemented through different practices toward soul purification such as tarekat and suluk. These practices are alive in the community not only in the rural area but also in the urban context. However, these lead to bring the community in the traditional ascetism as well as in the religious understanding. The latest then will be named as neo-sufism.